ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KEPEMILIKAN MAYORITAS TERHADAP AGRESIVITAS PAJAK (Studi Empiris Terhadap Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Erlang Purwanggono; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
The purpose of this study was to examine Corporate Social Responsibility and Majority Firm to Tax Aggressiveness. This study is a developing of a previous study, Lanis and Richardson (2011). The difference between this and previous studies is the use of samples and test equipment at research previous studies using a CSR method from Australia, measuring a Majority Firm with previous study from previous study in Indonesia. Whereas this study uses SPSS test equipment 21 The populations used in this study are  manufacturing company listed in the Indonesian Stock Exchange from year 2011-2013. Sampling technique in this study using purposive sampling method. Data analysis techniques performed by hypothesis testing using multiple linear regression method. The results of this study indicate that Corporate Social Responsibility negative  significantly influence Tax Aggressiveness. Whereas, Majority Firm also have a negative significant effect on the Tax Aggressiveness.